Students Understanding of Science in Using the Cognitive Thinking Skills Method With Online Learning as A Solution for Speaking Skills in The Era of Digital Technology - Susanto, Ferri; Zasrianita, Fera; Nadrah, Nadrah; Hamzah, Syukri (IJIS Edu : Indonesian Journal of Integrated Science Education, 2024)
The research examines the cognition of Foreign English (EFL) students using the Cognitive Thinking Skills method using online media as a solution for speaking skills in the digital era. The research method uses a mix method, namely: a sample of 20 students uses quantitative data analysis techniques to calculate validity and reliability, while qualitative data is analyzed based on Huberman and Miles' theory, namely collecting, reducing, verifying and displaying. The research results showed that students gave positive responses, learning felt easy and they were confident in practicing English with online media so that the development of students' cognition using the Cognitive Thinking Skill method was more adaptable and flexible. Questionnaire with a Likert scale, validity and reliability are calculated statistically: 45 items are tried out into 20 valid items, then whether the items are valid or not use the significance value (P-value) provided that if the significance value is < 0.05 then the item is valid and if significance value > 0.05 then the item is invalid. Cronbach's Alpha is significant at 0.758 > 0.21, meaning the data can be concluded to be reliable. The questionnaire instrument contains aspects of student cognition using the Cognitive Thinking Skills Method with three indicators, namely: thinking, judgment and decision. The percentage shows 45% of students gave a positive response. 25% of the total respondents to the online speaking class were in the very positive category and another 35% chose neutral. Percentage data can provide evidence that cognitive skills are a complex function of the human brain that involves aspects of memory, both short-term and long-term, attention, planning, and reasoning and strategies in a person's thinking.